Hole‐in‐the‐head disease in discus fish, Symphysodon (Heckel, 1840): Is it a consequence of a dietary Ca/P imbalance?. Issue 8 (26th May 2019) - Amesberger‐Freitag, Alessandra; Tichy, Alexander; El‐Matbouli, Mansour; Lewisch, Eva
Abstract: Hole‐in‐the‐head (HITH) disease‐affected fish develop characteristic lesions in the skin above sensory pores of the head and the trunk. This study investigated whether an unfavourable Ca/P ratio in the diet could provoke lesions consistent with HITH disease in discus fish Symphysodon (Heckel, 1840) as a comparable condition to secondary hyperparathyroidism of tetrapod species. Two groups of five fish were fed a plain beef heart diet (Ca/P of 0.03), whereas two other groups were kept on commercial discus feed (Ca/P of 2.73). Each feeding group was submitted to two different water hardness regimes (35.66–71.39 mg/L CaCO3 and 124.94–196.33 mg/L CaCO3, respectively). All fish were observed for the development of the characteristic lesions for 16 weeks. At the end of the study, histological, bacteriological and parasitological examinations were conducted and plasma Ca, P and Mg values were determined. Diplomonad flagellates were detected in two fish. Isolated bacteria of all groups mostly belonged to Aeromonadales and Pseudomonadales. No significant difference of plasma mineral values between the groups was observed. Compared to the results of other authors, Ca stayed mainly in the range and P exceeded the reference values. Histological examinations did not indicate HITH disease, and no fish developed signs of the disease during the study. Clinical trial registration number GZ 68.205/0135‐WF/V/36/2014.